Development of Innovative AR-Based Teaching Media Using The Assemblr-Edu Platform on Asset Material - Fityah Nabilah; Yusriyani Mulyawati; Aan Anisah (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This research aims to develop innovative learning media based on Augmented Reality (AR) using the Assemblr-Edu platform on asset material assisted with Canva media. This research uses the Research and Development (R&D) method with the 4D development model (Define, Design, Develop, and Disseminate). The research instrument is a questionnaire involving media experts, material experts, and student responses. The sample of research subjects consisted of five students of class XII SMK Veteran Cirebon. Based on the validation results, the developed media obtained a percentage of eligibility of 90% from media experts, 89% from material experts, and 95% from student responses. The results showed that the products produced were valid and able to increase students' interest in learning. Thus, this AR-based teaching media has the potential to be an innovative solution in learning accounting, especially in asset material.